A Hierarchy of Out-of-Equilibrium Actor-Based System-Dynamic Nonlinear conomic Models - Kovalevsky, Dmitry V.; Hasselmann, Klaus (Discontinuity, Nonlinearity, and Complexity, 2026)
The actor-based system-dynamic approach to macroeconomic modeling is illustrated for a simple model hierarchy consisting of a basic twodimensional model with several alternative three-dimensional extensions. The hierarchy is based on an out-of-equilibrium approach: market clearing is not assumed, supply is not equal to demand, and there exists a stock of unsold goods. Depending on actor behaviour, the models exhibit stable exponential growth or instabilities leading to nonlinear oscillations or economic collapse. In most cases, the simplicity and tractability of the models enables analytical solutions. The examples serve as illustration of more realistic models developed within the Multi-Actor Dynamic Integrated Assessment Model System (MADIAMS) to assess the long-term impacts of climate mitigation policies.